2006
DOI: 10.1902/jop.2006.060025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periodontitis on Biting Abilities

Abstract: Reduced periodontal support in the absence of inflammation negatively affected biting abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 11 publications
6
44
1
1
Order By: Relevance
“…Moreover, the role of satisfactory periodontal status can be explained because it is intuitive that high occlusal forces demand that teeth are firmly supported by healthy periodontal tissue [22]. According to Alkan et al [28], occlusal harmony exists when the various components of the masticatory system (teeth and supporting bone, temporomandibular joint, muscles, and ligaments) are healthy and can withstand the functional stress. Occlusal equilibrium is impaired by periodontal disease when the bone around the teeth is reduced, tooth mobility is increased, and teeth migrate [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the role of satisfactory periodontal status can be explained because it is intuitive that high occlusal forces demand that teeth are firmly supported by healthy periodontal tissue [22]. According to Alkan et al [28], occlusal harmony exists when the various components of the masticatory system (teeth and supporting bone, temporomandibular joint, muscles, and ligaments) are healthy and can withstand the functional stress. Occlusal equilibrium is impaired by periodontal disease when the bone around the teeth is reduced, tooth mobility is increased, and teeth migrate [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to Alkan et al [28], occlusal harmony exists when the various components of the masticatory system (teeth and supporting bone, temporomandibular joint, muscles, and ligaments) are healthy and can withstand the functional stress. Occlusal equilibrium is impaired by periodontal disease when the bone around the teeth is reduced, tooth mobility is increased, and teeth migrate [28]. The disadvantage of adopting these new definitions is the more restrictive nature of these conditions and the need to add new items to clinical exams performed in studies, such as occlusal contact between posterior teeth, to allow the evaluation of oral status not to be restricted to counting the number of teeth present.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory signals from the periodontal ligament are important for the regulation of bite strength. In previous studies, alterations in probing depth and insertion level were found to be significantly correlated with a reduction in bite force (7,19). An explanation for this is based on the belief that the loss of periodontal support results in compromised modulation of masticatory forces (5).…”
Section: Discussionmentioning
confidence: 88%
“…The periodontal examination involved measuring pocket depth with a manual periodontal probe (Hu-Friedy PCP-UNC 15, Hu-Friedy, Chicago, IL, USA) to the nearest millimeter. The mean values of each patient were considered for statistical purposes (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation